Breast Reconstruction Does Not Affect the Survival of Patients with Breast Cancer Located in the Central and Nipple Portion: A Surveillance, Epidemiology, and End Results Database Analysis - Xiong, Mingchen; Liu, Zeming; Lv, Wenchang; Zhao, Chongru; Wang, Yichen; Tan, Yufang; Zhang, Qi; Wu, Yiping; Zeng, Hong (Frontiers in Surgery, 2022)
Background Tumors in the central and nipple portion (TCNP) are associated with poor prognosis and aggressive clinicopathological characteristics. The availability and safety of postmastectomy reconstruction in breast cancer patients with TCNP have still not been deeply explored. It is necessary to investigate whether reconstruction is appropriate for TCNP compared with non-reconstruction therapy in terms of survival outcomes. Methods Using the Surveillance, Epidemiology, and End Results (SEER) database, we enrolled TCNP patients diagnosed between the years 2010 and 2016. The propensity score matching (PSM) technique was applied to construct a matched sample consisting of pairs of non-reconstruction and reconstruction groups. Survival analysis was performed with the Kaplan–Meier method. Univariate and multivariate Cox proportional hazard models were applied to estimate the factors associated with breast cancer-specific survival (BCSS) and overall survival (OS). Results In the overall cohort, a total of 6,002 patients were enrolled. The patients in the reconstruction group showed significantly better BCSS (log-rank, p < 0.01) and OS (log-rank, p < 0.01) than those in the non-reconstruction group (832 patients) after PSM. However, the multivariate Cox regression model revealed that breast reconstruction was not associated with worse BCSS and OS of TCNP patients. Conclusion Our study provided a new perspective showing that breast reconstruction did not affect the survival and disease prognosis in the cohort of TCNP patients from SEER databases, compared with non-reconstruction. This finding provides further survival evidence supporting the practice of postmastectomy reconstruction for suitable TCNP patients, especially those with a strong willingness for breast reconstruction.